STRATEGIES IN DEVELOPING ENGLISH AND INDONESIAN ACADEMIC WRITING BY EFL STUDENTS - Teguh Budiharso (Center of Language and Cultural Studies, 2014)
This study was aimed at seeing the writing strategies used by EFL Undergraduate students at Muhammadiyah University of Malang. This study used content analysis as the design, focusing on the quality of rhetoric and strategies in developing English academic essays written in Bahasa Indonesia and in English Language. The study assigned 10 students as the subject of the study. Data of this study included English and Indonesian essays, answers of questionnaires and responses of interview given to the 10 students. The study revealed that good writers wrote linear essays in Bahasa Indonesia and in English language. In writing practices and strategies, poor writers did not write draft of the essays, did not revise, and did not edit the essays, either. Good writers, on the contrary did make drafting, revising, and editing before final copy of an essay was achieved. In addition, reading references were also influential for the good writers to improve writing style and quality of the content of the essays, but not for the poor ones.